Standardisation of technological innovations in agriculture: Avenues for future research on co-regulation - Glaa, Besma; Fried, Andrea; Frankelius, Per (Journal of Standardisation, 2023)
Co-regulation involves consulting different stakeholders on the key aspects of a regulatory process. The aim of this explorative study is to examine current challenges of co-regulation drawing on the example of standardization in the context of agricultural innovations and to point out avenues for future research. To this end, we reviewed current literature on co-regulation and compiled interviews with experts from agriculture on the challenges of co-regulation especially in standardization. Four research questions, which we regard as central, could be derived. Two questions deal with the standardization work of technical committees on technological innovations in agriculture, and two questions relate to the agricultural businesses that the standards eventually implement.